2019
DOI: 10.1002/1873-3468.13387
|View full text |Cite
|
Sign up to set email alerts
|

miR‐134 inhibits osteosarcoma cell invasion and metastasis through targeting MMP1 and MMP3 in vitro and in vivo

Abstract: miR‐134 has been shown to be associated with angiogenesis and the progression of osteosarcoma. This study further assessed the effects of miR‐134 expression on osteosarcoma cell migration, invasion, and metastasis in vitro and in a nude mouse xenograft model, exploring the underlying molecular events. Luciferase reporter assays revealed that miR‐134 directly targets the 3′‐UTRs of MMP1 and MMP3 to reduce their expression in osteosarcoma cells. In conclusion, overexpression of miR‐134 suppresses osteosarcoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 54 publications
4
30
0
Order By: Relevance
“…We found that in addition to KLF4 and BMI1, miR-135a also inhibited the expression of MMP2 and MMP9, as shown by Western blot, and inhibited MMP activation, as shown by the decrease in the intensity of MMPSense in FMT, which plays important roles in promoting tumor invasion and metastasis. These data are consistent with our previously published study (8). Meanwhile, Zheng et al (38) showed that the decrease in MMP2 and MMP9 protein levels induced by DANCR silencing was partially increased by the miR-135a-5p inhibitor, which supports our result that miR-135a inhibits MMP2 and MMP9.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that in addition to KLF4 and BMI1, miR-135a also inhibited the expression of MMP2 and MMP9, as shown by Western blot, and inhibited MMP activation, as shown by the decrease in the intensity of MMPSense in FMT, which plays important roles in promoting tumor invasion and metastasis. These data are consistent with our previously published study (8). Meanwhile, Zheng et al (38) showed that the decrease in MMP2 and MMP9 protein levels induced by DANCR silencing was partially increased by the miR-135a-5p inhibitor, which supports our result that miR-135a inhibits MMP2 and MMP9.…”
Section: Discussionsupporting
confidence: 93%
“…MicroRNAs (miRNAs) are a family of small, noncoding RNA molecules that regulate gene expression at the posttranscriptional level through either mRNA cleavage or translational repression through direct binding to the 3′ untranslated region (3′-UTR) (25,26). Our previous studies indicated that upregulation of some miRNAs could intensely restrain the growth, invasion, and metastasis in OS xenograft tumors and attenuate angiogenesis (8,27). We also found that the level of miRNA-135 (miR-135a-5p) was reduced in OS tissues from patients in whom BMI1, KLF4, and MMP expression was upregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been reported in context of miR-134 mediated tumour regulation. In osteosarcoma, the upregulation of miR-134 reportedly inhibits cell invasion and metastasis via the suppression of MMP1 and MMP3 expression [26]. In addition, miR-134 is reported to impede EMT and reduce the invasive potential of NSCLC cells [27] and inhibit the growth of NSCLC by targeting the epidermal growth factor receptor [28].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-134-5p can also be targeted and regulated by lncRNA [32, 33]. Studies have found that miR-134-5p exerts anti-tumour effects by affecting target gene expression in osteosarcoma [3436]. This study demonstrated that miR-134-5p was regulated by lncRNA TTN-AS1 to inhibit osteosarcoma growth and apoptosis.…”
Section: Discussionmentioning
confidence: 81%